The levels of circulating long non-coding RNA GAS5 in prostate carcinoma patients: a single-center study - Mišović, Miroslav; Aleksić, Predrag; Kostić, Dejan; Vuković, Miodrag; Radojičić, Bojan; Rančić, Nemanja; Cikota Aleksić, Bojana (Vojnosanitetski pregled, 2023)
Background/Aim. Prostate carcinoma (PCa) is second occurring carcinoma that affects the male population. Although PCa incidence rates are high, most cases have a favorable prognosis, with comfortable long-term life quality. The aim of the study was to compare long non-coding RNA (lncRNA) growth arrest-specific transcript 5 (GAS5) plasma levels between healthy individuals and patients with PCa, and also between PCa patients with different prognostic scores. Methods. The present study included a total of 40 patients with PCa and a control group of 20 healthy individuals. PCa patients were divided into two subgroups (20 patients each) based on the prognostic criteria of the American Joint Committee on Cancer. The patient data were collected and analyzed; lncRNA GAS5 levels were quantified using the real-time polymerase chain reaction method. Statistical analysis was conducted using the IBM SPSS Statistics 26.0 computer program (IBM, USA, 2019). Results. The relative quantification of lncRNA GAS5 expression levels showed downregulation in PCa patients compared to healthy individuals; however, the difference was marginally statistically significant (p = 0.056). With further analysis of the given results, we concluded that the expression level of lncRNA GAS5 was not significantly different in the first patient subgroup and the healthy individuals (p = 0.268). Patients from the second subgroup had significantly lower plasma levels of lncRNA GAS5 than healthy individuals (p = 0.033). The difference in the level of lncRNA GAS5 expression between patients with favorable prognoses (Group 1) and the ones with worse prognostic scores (Group 2) did not indicate statistical significance (p = 0.275). In both Group 1 (p = 0.805) and Group 2 (p = 0.454), the plasma levels of lncRNA GAS5 were not significantly different in comparison to the age (≤ 65 vs. > 65 years). Conclusion. One of the main objectives of PCa research is identifying novel and more efficient biomarkers. Conducted research provides strong evidence about the significance of lncRNAs GAS5 in PCa, as well as the correlation between decreased expression of lncRNA GAS5 and poor prognosis in various tumors.
Keywords: biomarkers; prognosis; prostate neoplasms; rna, long noncoding